Kontrol Diri dalam Adiksi Judi Online di Desa Brang Kolong - Arisanti, Ivon; Arjuansyah (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2024)
Self-control is needed so that individuals can regulate, direct and guide behavior which ultimately leads to the desired positive consequences. Self-control provides decisions through conscious consideration to integrate actions taken to achieve the results and goals desired by each individual. Self-control has one's readiness to behave in accordance with the demands of norms, customs and values. This research uses a qualitative approach, where the data obtained in the research will be described descriptively. Qualitative Research is research that has quite complex characteristics which aims to explore and tell the experiences of someone involved in an incident. Self-control is an individual's ability to control desired and unwanted information, a person's ability to choose actions based on what he believes, and the ability to change behavior. People with strong self-control are generally more successful in various aspects of life. Based on the findings in the field which have been presented in the results and discussion chapter, a conclusion can be drawn which shows that subjects who experience online gambling addiction tend to be unable to control themselves from playing online gambling. As a result, there are deviant social phenomena, such as behavior that is contrary to societal norms and values, known as social disease or social pathology.